2023
DOI: 10.1200/jco.2023.41.16_suppl.e16554
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-pathological features and treatment outcomes in Hispanic/Latino patients with advanced renal cell carcinoma at a single institution.

Abstract: e16554 Background: Annually, there are over 400,000 new renal cell carcinoma (RCC) cases and more than 170,000 deaths worldwide. RCC is one of the top ten more prevalent malignancies in the United States, with 76,000 new cases each year and almost 14,000 deaths. Over the past half-century, RCC has more than doubled in incidence. Studies demonstrate histologic differences and outcome disparities among Hispanic and Latino patients diagnosed with RCC. Research to date describes earlier and more advanced diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some studies have shown a nearly three-fold increase in the incidence of renal RCC among Hispanics 60,61 . This rise may be linked to disparities in disease presentation, with Hispanics showing higher rates of metastatic disease at diagnosis and more advanced stages of RCC compared to non-Hispanic/Latino individuals 62,63 . Additionally, differences in access to care, including insurance coverage and country of birth, have been noted, impacting the age of diagnosis, treatment choices, and outcomes among Hispanic RCC patients 64 .…”
Section: Incidence Trends By Race/ethnicitymentioning
confidence: 99%
“…Some studies have shown a nearly three-fold increase in the incidence of renal RCC among Hispanics 60,61 . This rise may be linked to disparities in disease presentation, with Hispanics showing higher rates of metastatic disease at diagnosis and more advanced stages of RCC compared to non-Hispanic/Latino individuals 62,63 . Additionally, differences in access to care, including insurance coverage and country of birth, have been noted, impacting the age of diagnosis, treatment choices, and outcomes among Hispanic RCC patients 64 .…”
Section: Incidence Trends By Race/ethnicitymentioning
confidence: 99%